SISTEM INFORMASI GEOGRAFIS (SIG) FASILITAS – FASILITAS YANG ADA DI KOTA BENGKULU BERBASIS WEB - Asnawati, Asnawati; Kusuma, Galih Putra (UNIVED Press, 2011)
Geographic Information Systems Facilities - Existing Facilities in Bengkulu city developed as a system that provides information about the city of Bengkulu in the form of vector data is intact, web-based, dynamic and interactive so that users can access information through the Internet and interact with the system directly. Information presented in the form of spatial data and attribute that includes the city of Bengkulu district, roads, rivers, government facilities, public services, central business and tourism. Facilities are shown as points on a polygon-shaped region. The system was developed using version 0.96 as ALOV Folder WebGIS application based on Java, DBF as the database. ALOV Folder supports complex GIS architecture, and able to work with multilayer. The system provides several tools that are required to interact with maps such as choosing a domain map, theme maps, perform a search (search) to see information related to the location, activate the layer, the legend of the map, zoom in, zoom out, pan, select, and hyperlinks